Analysis of Community Relations Practice for Peaceful Coexistence between Organisations and Host Communities - ZANNU, Prosper Nunayon; TALABI, Felix Olajide; AIYESIMOJU, Ayodeji Boluwatife; BELLO, Samson Adedapo; OYEDEJI, Kazeem Alade; OGUNDEJI, Benjamin Kayode; ADEJOH, Reuben; ADENIRAN, Pauline Oghenekaro; ADEJOH, Monday (Journal of Ecohumanism, 2024)
The study investigated why organisations fail to achieve mutually peaceful relationships despite huge investments in community relations programmes using Brass Liquefied Natural Gas Limited in Brass Island, Bayelsa State and the Whispering Palms, a privately owned holiday resort in Iworo-Ajido, Badagry, Lagos State as a case study. The study was predicated on the Social Penetration theory of public relations. With a survey of 370 respondents, the study revealed that Brass Liquefied Natural Gas Limited enjoys a smooth working relationship with the Brass Island communities because of the high level of acceptance of and participation in Brass Liquefied Natural Gas Limited community relations programmes by the members of the host community. The study concludes that the organisational goal of mutual and peaceful coexistence between host communities and organisations does not depend solely on huge investment in community relations programmes. Rather, the host communities' acceptance of the community relations programmes and their participation in executing such programmes are required.